ANALISIS PENGARUH GAJI, INSENTIF DAN REWARD TERHADAP KINERJA KARYAWAN PT BPRS MITRA HARMONI KOTA MALANG - Mohammad Makhmud; Yunus Handoko; Sudjilah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
Banking performance, especially Sharia People's Economic Banks after the Covid 19 pandemic, has not fully recovered. Although the economy is gradually improving, it has not been able to provide a stimulus for banking growth. During the last 3 years, the performance of the Islamic BPR industry both nationally and regionally in East Java, both from Assets, Financing and Third Party Funds, has decreased in percentage terms. Likewise, the quality of financing has also deteriorated, indicated by the Non Performing Finance ratio which continues to increase from year to year, one of which is caused by conditions after the Covid 19 pandemic. The purpose of this study was to determine and analyze the effect of salary, incentives and rewards on employee performance. The sample selection technique used total sampling with 40 respondents. The data collection technique used is a questionnaire. The analysis technique uses multiple linear regression with SPSS for windows 26.0 statistical analysis. The results showed that there was a significant positive effect of salary and incentives on employee performance, but there was no effect of rewards on employee performance.